Low incidence of anti‐drug antibodies in patients with type 2 diabetes treated with once‐weekly glucagon‐like peptide‐1 receptor agonist dulaglutide. Issue 5 (4th March 2016) - Milicevic, Z.; Anglin, G.; Harper, K.; Konrad, R. J.; Skrivanek, Z.; Glaesner, W.; Karanikas, C. A.; Mace, K.
Abstract : Therapeutic administration of peptides may result in anti‐drug antibody (ADA) formation, hypersensitivity adverse events (AEs) and reduced efficacy. As a large peptide, the immunogenicity of once‐weekly glucagon‐like peptide‐1 (GLP‐1) receptor agonist dulaglutide is of considerable interest. The present study assessed the incidence of treatment‐emergent dulaglutide ADAs, hypersensitivity AEs, injection site reactions (ISRs), and glycaemic control in ADA‐positive patients in nine phase II and phase III trials (dulaglutide, N = 4006; exenatide, N = 276; non‐GLP‐1 comparators, N = 1141). Treatment‐emergent dulaglutide ADAs were detected using a solid‐phase extraction acid dissociation binding assay. Neutralizing ADAs were detected using a cell‐based assay derived from human endothelial kidney cells (HEK293). A total of 64 dulaglutide‐treated patients (1.6% of the population) tested ADA‐positive versus eight (0.7%) from the non‐GLP‐1 comparator group. Of these 64 patients, 34 (0.9%) had dulaglutide‐neutralizing ADAs, 36 (0.9%) had native‐sequence GLP‐1 (nsGLP‐1) cross‐reactive ADAs and four (0.1%) had nsGLP‐1 neutralization ADAs. The incidence of hypersensitivity AEs and ISRs was similar in the dulaglutide versus placebo groups. No dulaglutide ADA‐positive patient reported hypersensitivity AEs. Because of the low incidence of ADAs, it was not possible to establish their effect on glycaemic control.